Mammalian Neuraminidases in Immune-Mediated Diseases: Mucins and Beyond - Lillehoj, Erik P.; Luzina, Irina G.; Atamas, Sergei P. (Frontiers in Immunology, 2022)
Mammalian neuraminidases (NEUs), also known as sialidases, are enzymes that cleave off the terminal neuraminic, or sialic, acid resides from the carbohydrate moieties of glycolipids and glycoproteins. A rapidly growing body of literature indicates that in addition to their metabolic functions, NEUs also regulate the activity of their glycoprotein targets. The simple post-translational modification of NEU protein targets—removal of the highly electronegative sialic acid—affects protein folding, alters protein interactions with their ligands, and exposes or covers proteolytic sites. Through such effects, NEUs regulate the downstream processes in which their glycoprotein targets participate. A major target of desialylation by NEUs are mucins (MUCs), and such post-translational modification contributes to regulation of disease processes. In this review, we focus on the regulatory roles of NEU-modified MUCs as coordinators of disease pathogenesis in fibrotic, inflammatory, infectious, and autoimmune diseases. Special attention is placed on the most abundant and best studied NEU1, and its recently discovered important target, mucin-1 (MUC1). The role of the NEU – MUC axis in disease pathogenesis is discussed, along with regulatory contributions from other MUCs and other pathophysiologically important NEU targets.